2019
DOI: 10.18052/www.scipress.com/sfp.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of Cassava Processing: A Case Study of Otukpo Lga, Benue State, Nigeria

Abstract: The study investigated the economics of cassava processing in Otukpo Local Government Area, Benue State, Nigeria. Data were collected using well-structured questionnaire administered to 60 cassava processors. Data collected were analyzed using descriptive statistics, Profit function, independent sample t-test and Analysis of Variance (ANOVA). Results showed that majority of the processors were within the age group of 31–40 years with mean year of experience of 34 years. They were mostly women with an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
3
5
1
Order By: Relevance
“…Processing of cassava into garri product would likely due to the fact that garri is most consumed cassava product in the study area. This however, disagrees with the findings of [23] who reported that most processors engage in garri and fufu production. A relative high percentage of the respondents (32.3%) also engaged in garri and fufu production because consumption of the food types is a prominent local diet in the study area.…”
Section: Cassava Processing Activitiescontrasting
confidence: 99%
“…Processing of cassava into garri product would likely due to the fact that garri is most consumed cassava product in the study area. This however, disagrees with the findings of [23] who reported that most processors engage in garri and fufu production. A relative high percentage of the respondents (32.3%) also engaged in garri and fufu production because consumption of the food types is a prominent local diet in the study area.…”
Section: Cassava Processing Activitiescontrasting
confidence: 99%
“…The result further indicates that the sales of garri by wholesalers was most profitable (N2,324,071.20) in the study area followed by the sales of fufu (N 1,997,385). This corroborates (Ani et al, 2019) who opine that net profits derived from processing Cassava into garri was significantly higher than other cassava value added products. However, the least profitable was the sales of the cassava stem cuttings with an average profit of N294,601.…”
Section: Distribution Of Cost and Returns Of Wholesalers Of Cassava P...supporting
confidence: 88%
“…This means that cassava production is a profitable venture. This made valid the report of Ani, et al [4], who stated that cassava production is a profitable venture when properly managed. It also supports the finding of UN COMTRADE [5], which reported that in Thailand cassava increasing yields over the past two decades have boosted small-holder earnings by an estimated US$650 million and lifted many cassava growers out of poverty.…”
Section: Discussionsupporting
confidence: 70%